2014
DOI: 10.1096/fj.13-233593
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal expression of I‐TAC (Cxc111) instructs adaptive Th2‐type immunity

Abstract: To decipher early promoters of the local microenvironment for Th2-type immunity, we wanted to identify gene patterns that were induced by Leishmania major in the infected skin of susceptible, Th2-prone BALB/c, but not of resistant, Th1-prone C57BL/6 mice. We found a marked up-regulation of the chemokine I-TAC (Cxcl11) during the first 2 d of infection in the epidermis of susceptible but not of resistant mice. Accordingly, local injection of I-TAC (2×1 μg) in resistant mice on the first day of infection resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Although neutrophils may be a possible vehicle for Leishmania , facilitating infection, it was described that exacerbated neutrophil recruitment is associated with parasite killing ( 162 ). On the other way, it was also shown that skin lesions of L. major infected mice mainly contained Th2 cell-attracting chemokines, such as CCL7 ( 163 , 164 ). The absence of Th1 cell-attracting chemokines in these lesions may reflect the downregulation of the expression of genes linked with Th1 trafficking, such as the ones coding for CXCR3 chemokines ( 165 ).…”
Section: Modulating the Immune Response Through Alteration Of Cytokinmentioning
confidence: 99%
“…Although neutrophils may be a possible vehicle for Leishmania , facilitating infection, it was described that exacerbated neutrophil recruitment is associated with parasite killing ( 162 ). On the other way, it was also shown that skin lesions of L. major infected mice mainly contained Th2 cell-attracting chemokines, such as CCL7 ( 163 , 164 ). The absence of Th1 cell-attracting chemokines in these lesions may reflect the downregulation of the expression of genes linked with Th1 trafficking, such as the ones coding for CXCR3 chemokines ( 165 ).…”
Section: Modulating the Immune Response Through Alteration Of Cytokinmentioning
confidence: 99%
“…Keratinocytes may thus induce Th1 cell polarization in resistant mice. By contrast, the production of interferon‐inducible T‐cell alpha chemokine 1 (iTAC), which reduces IL‐12 expression by DCs, is enhanced in L. major ‐infected susceptible mouse keratinocytes (Figure ). L. infantum up‐regulates, but L. major inhibits, the expression of pro‐inflammatory cytokines such as IL‐6, IL‐8, TNF‐α, and IL‐1β in keratinocytes (Figure ).…”
Section: Leishmaniasis and Immune Responsementioning
confidence: 99%
“…In a model of L. ( L. ) major , expression of immunomodulatory mediators involved in T H 1 induction were significantly highly induced in keratinocytes isolated from the infected skin of resistant mice and several were enriched in the epidermis upon RNA in situ hybridization, suggesting keratinocytes may be a rich source of skin derived cytokines in vivo [ 44 ]. Interferon-inducible T-cell alpha chemokine 1 (I-TAC), an early released cytokine that antagonized IL-12 production by DCs, is significantly increased in the epidermis and keratinocytes of susceptible compared to resistant mice infected with L. ( L. ) major [ 224 ]. Experiments performed in our lab suggest Leishmania species causing divergent clinical disease elicit distinct inflammatory responses by human keratinocytes in vitro.…”
Section: Cellular Determinants Of the Immune Response In Murine Cumentioning
confidence: 99%